2001
DOI: 10.1073/pnas.211341698
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts are required for GLUT4 internalization in adipose cells

Abstract: We have assessed the role of lipid rafts on GLUT4 traffic in adipose cells. High GLUT4 levels were detected in caveolae from adipocytes by two approaches, the mechanical isolation of purified caveolae from plasma membrane lawns and the immunogold analysis of plasma membrane lawns followed by freeze-drying. The role of lipid rafts in GLUT4 trafficking was studied by adding nystatin or filipin at concentrations that specifically disrupt caveolae morphology and inhibit caveolae function without altering clathrin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 36 publications
(37 reference statements)
2
78
0
Order By: Relevance
“…A number of transporters appear to use lipid rafts and lipid raft localized t-SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptors) and v-SNARE proteins as a means to direct their trafficking to the correct cellular compartment (29,30). In a study of GLUT4 trafficking in 3T3-L1 adipocytes, SNAP23 and syntaxin 4 were associated with plasma membrane rafts while VAMP2 was primarily in intracellular lipid raft membranes.…”
Section: Resultsmentioning
confidence: 99%
“…A number of transporters appear to use lipid rafts and lipid raft localized t-SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptors) and v-SNARE proteins as a means to direct their trafficking to the correct cellular compartment (29,30). In a study of GLUT4 trafficking in 3T3-L1 adipocytes, SNAP23 and syntaxin 4 were associated with plasma membrane rafts while VAMP2 was primarily in intracellular lipid raft membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Caveolar and noncaveolar rafts together with their constituent proteins coisolate by isopycnic floatation as low-buoyant density membrane fractions (10) obtained after cold detergent extraction (8,12) or detergent-free extraction and sonication (13)(14)(15), and both are disrupted by cholesterol depletion (16,17), currently achieved by cyclodextrins (18). Cholesterol depletion experiments have suggested that raft integrity is needed for protein trafficking along certain steps of the exocytic (12,19) and endocytic (20)(21)(22)(23) pathways as well as for signal transduction (10,17).…”
mentioning
confidence: 99%
“…Components of insulin signaling are constitutively localized in lipid rafts, including some or all of the insulin receptor (Gustavsson et al, 1999;Kimura et al, 2002), flotillin (Baumann et al, 2000;Liu et al, 2005), and TC10 , which is specifically activated by insulin in these microdomains due to the recruitment of the exchange factor C3G via the tyrosine phosphorylation of c-Cbl and Cbl-b (Liu et al, 2003). Disruption of lipid rafts with cholesterol-extracting drugs such as beta-cyclodextrin or by overexpression of dominant-negative forms of caveolin block the actions of insulin, without disrupting other cellular functions (Gustavsson et al, 1999;Parpal et al, 2001;Ros-Baro et al, 2001;Shigematsu et al, 2003). Moreover, introduction of a modification of TC10 that prevents lipid raft association blocks the activation of the G protein by insulin, as well as the stimulation of glucose uptake in fat cells .…”
Section: Discussionmentioning
confidence: 99%